Tindak Pidana Bullying yang dilakukan Anak dibawah Umur melalui Keadilan Restorative Justice - I Made Rai Dwi Surya Atmaja; Anak Agung Sagung Laksmi Dewi; ni made sukaryati Karma (Jurnal Interpretasi Hukum, 2020)
Bullying is bullying that often leads to bad deeds that contain crime, but goes unnoticed. Based on this research, the authors raise the formulation of the problem: 1. How is legal protection for child victims of bullying ?, 2. How is the settlement of bullying crime through restorative justice? This type of research is normative law. The approach to this research problem is a statutory approach, a conceptual approach, and a case approach. The research method used is normative legal research, by conducting studies based on legal materials from legal books and is a process of finding legal rules. As for the problem approach in this study, namely the statutory approach (statute approach) and the conceptual approach (conceptual approach) and the case approach (case approach). The results show that the form of legal protection for child victims of criminal acts of bullying is regulated in several laws and regulations, namely, the Criminal Code, Law Number 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. Efforts to resolve criminal acts of bullying through restorative justice using non litigation or settlement of disputes outside the court. The point of settlement of cases on restorative justice is based on the parties to express their opinions to produce an agreement. There are two kinds of crime prevention efforts, namely penal and non-penal efforts. It is hoped that the government, agencies engaged in law enforcement and education as well as the public will make firm efforts against the crime of bullying.